Robert Spencer on Prophet of Islam: An appraisal of “The Truth about Muhammad” - Tariq Aziz; Dr. Muhammad Shahbaz Manj; Saima Shahbaz Manj (Al-Qamar, 2018)
Opposition to Islam and the Prophet of Islam is widespread in Western scholars and orientalists. One of the prominent persons in this list is Robert Spencer, a renowned anti-Islam American author and blogger. Spencer has studied the life and teachings of Muhammad (ﷺ) with aggressive criticism and religious prejudice. This paper evaluates some of the objections raised by Robert Spencer in his book “The Truth about Muhammad.” The themes of the book have been refined and security scrutinized carefully in maintaining the sanctity of Islam and respecting the rights of the Prophet of Islam. After a thorough analysis this paper finds that Robert Spence’s views are not based on objective study of the relevant sources.